Digital Financial Inclusion and Its Effect on SME Financial Performance: Evidence from Indonesia - Hidayat, Agus Rohmat; Hardiyanto, Feri; Alifah, Nur; Rosdiansjah, Agis Ahmad (GEMA EKONOMI, 2026)
Background: Digital financial inclusion (DFI) has emerged as a critical enabler of SME financial performance in developing economies, yet empirical evidence on its direct and mediated effects through organizational capabilities remains limited.Objective: This study aims to examine the direct and indirect effects of digital financial inclusion measured through mobile banking adoption, digital payment systems, and access to digital credit on SME financial performance, with organizational agility and digital transformation capability as mediating variables.Methods: A quantitative research design was employed using data collected from 312 SME owners and managers across four provinces in Indonesia through structured questionnaires. The data were analyzed using Structural Equation Modeling with Partial Least Squares (PLS-SEM).Results: The findings reveal that digital financial inclusion has a significant positive direct effect on SME financial performance (β = 0.412, p < 0.001). Organizational agility partially mediates this relationship (indirect effect β = 0.183, p < 0.01), while digital transformation capability fully mediates the relationship in technology-intensive sub-sectors (indirect effect β = 0.217, p < 0.001).Conclusion: This study highlights the strategic role of digital financial inclusion in enhancing SME performance through organizational capabilities. The results contribute to fintech and SME development literature and provide practical implications for policymakers to bridge the digital finance gap in emerging markets.